Increasing the concentration of woody biomass in the furnace room according to the characteristics and conditions of ignition; Journal of the Energy Institute; Vol. 101 - Kuznetsov G. V. Geny Vladimirovich; Syrodoy S. V. Semen Vladimirovich; Kostoreva A. A. Anastasiya Andreevna; Kostoreva Zh. A. Zhanna Andreevna; Purin M. V. Mikhail Vladimirovich; Malyshev D. Yu. Dmitry Yurievich (2022, 2022)
Title screen